Pragmatic frames, the thetic-categorical distinction and Spanish constituent order - Matínez Caro, Elena (ALFA: Revista de Linguística, 2009)
Spanish constituent ordering has been often characterised as the result of the interplay of discourse-pragmatic, semantic and syntactic factors. The purpose of this paper is to investigate constituent ordering in Spanish taking into account a series of pragmatic and semantic considerations as generally discussed in Functional (Discourse) Grammar. More particularly, constituent ordering in Spanish will be analysed from the perspective of the proposal made by Hannay (1991) on the modes of message management in the framework of Functional Grammar and the related distinction of thetic-categorical judgements, plus other areas in Functional Discourse Grammar such as the assignation of pragmatic functions and the establishment of special positions. The research for this study is based on the analysis of two sets of material of Peninsular Spanish, describing the language of adult educated native speakers.